2020
DOI: 10.18684/bsaa(19)180-190
|View full text |Cite
|
Sign up to set email alerts
|

Extracto de taninos del fruto piñón de oreja (Enterolobium cyclocarpum) como curtiente para piel de conejo común (Oryctolagus cuniculus)

Abstract: Los taninos son metabolitos secundarios producidos por el fruto piñón de oreja que pueden formar complejos con otras macromoléculas e incrementar la preservación de las pieles animales posterior al proceso de curtido. Este trabajo se enfocó en la extracción y cuantificación de taninos vegetales en el fruto piñón de oreja (Enterolobium cyclocarpum) para su potencial aplicación como curtiente en la piel de conejo raza Nueva Zelanda (Oryctolagus cuniculus). Para ello, se realizaron extracciones utilizando solucio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The studies showed that the two concentrations of ethanol (70% ethanol/30% water and 50% ethanol/50% water) are ideal for the extraction of tannins, giving a dark green coloration in the precipitate of the solution with mango kernel (7), which suggest the presence of condensed tannins, as well as Maryati et al (12) and Sánchez-García et al (32) that indicate that the addition of ferric chloride makes the tannin form complex compounds with Fe +3 ions. Similar results were obtained by Paz-Díaz et al (2), who compared the solvents acetone, ethanol and methanol for the extraction of tannins from the fruit of the Piñón de Oreja tree; this research found that ethanol has a greater capacity to extract tannins in parts of plant material. The qualitative results of these investigations demonstrated the applicability of these plant material for use in leather tanning (28).…”
Section: Qualitative Analysis Of Tanninssupporting
confidence: 87%
See 1 more Smart Citation
“…The studies showed that the two concentrations of ethanol (70% ethanol/30% water and 50% ethanol/50% water) are ideal for the extraction of tannins, giving a dark green coloration in the precipitate of the solution with mango kernel (7), which suggest the presence of condensed tannins, as well as Maryati et al (12) and Sánchez-García et al (32) that indicate that the addition of ferric chloride makes the tannin form complex compounds with Fe +3 ions. Similar results were obtained by Paz-Díaz et al (2), who compared the solvents acetone, ethanol and methanol for the extraction of tannins from the fruit of the Piñón de Oreja tree; this research found that ethanol has a greater capacity to extract tannins in parts of plant material. The qualitative results of these investigations demonstrated the applicability of these plant material for use in leather tanning (28).…”
Section: Qualitative Analysis Of Tanninssupporting
confidence: 87%
“…Each skin was then added in a solution of 3 L of water with 1 mL of 10% sulfuric acid H 2 SO 4 (%w/v) and remained at rest for 60 minutes in order to break the collagen fibers to subsequently add 10 mL of formaldehyde to 3% and fix the hair on the skin. After this time, the skins were rinsed with plenty of water to remove the acid and formaldehyde, and the epidermis was removed from the skin (2,30). For tanning, the skins were immersed in 3 L of tannin solution (20 mL of tannin extract in 1 L of water, corresponding to the mL of tannin extract from the extraction of the 50/50 and 70/30 %v/v concentrations) for 3 days, shaking twice a day for greater fixation of the tannin in the skin.…”
Section: Ovine Tanning Processmentioning
confidence: 99%
“…Uno de los métodos más utilizados para extraer polifenoles a partir de vegetales y residuos sólidos agroindustriales es la extracción con solventes (8), conocida también como extracción sólidolíquido. Los solventes más utilizados han sido agua acidificada, etanol, metanol y acetona (9). Numerosos trabajos de investigación han estudiado la extracción de compuestos bioactivos (entre ellos los polifenoles) como alternativa de valorización de residuos vegetales (10).…”
Section: Introductionunclassified